When Intuition Fails us: the World Wide Web as a Corpus - Scheffler, Paweł (Wydawnictwo Naukowe UAM, 2007)
In some respects corpus linguistics has made a significant contribution to foreign language (L2) instruction: for example, reference tools like dictionaries and grammar books are at present enriched by various types of information derived from corpora. However, as far as teachers' and students' use of corpora is concerned, the impact of corpus linguistics has been rather limited. This article demonstrates how teachers and learners of English as a foreign language can use the World Wide Web as a corpus. More specifically, it shows how the WWW can help teachers and learners in making L2 acceptability judgements.
Keywords: World Wide Web; Corpus